Effects of Soft Tissue Massage Along with Mobilization Technique on Intensity of Symptoms and Functional Status of Carpal Tunnel Syndrome: A Randomized Controlled Trial : Effects of Soft Tissue Massage - Syed, Hamna; Ahmed, Syed Imran; Arif, Abida; Zia, Madiha; Shahbaz, Naila Naeem; Kashif, Muhammad (Pakistan Journal of Health Sciences, 2023)
The median nerve in the wrist is compressed in the carpal tunnel, causing Carpal Tunnel Syndrome (CTS). The symptoms of this condition include numbness, tingling, and pain in the hand and fingers. The effectiveness of soft tissue massage along with mobilization techniques in managing CTS symptoms and improving functional status is an area to explored. Objective: To determine the effects of soft tissue massage along with mobilization technique on intensity of pain and functional status in Carpal tunnel syndrome patients. Methods: A randomized controlled trial was conducted on 60 patients with mild and moderate carpal tunnel syndrome at Sindh Institute of Physical Medicine and Rehabilitation, Karachi. In group A, soft tissue massage (Medenci hand massage technique) was combined with joint (radiocarpal and inter-carpal) and median nerve mobilization sliders, whereas in group B, only joint and median nerve mobilization sliders were used. A visual analog pain scale, the Boston scale of carpal tunnel syndrome, a dynamometer and a pinch gauge were used to evaluate participant on day 1 and the last treatment session. Results: There was no significant difference between group A and B after treatment. However, there was significant improvement (p<0.05) in intragroup analysis in all outcome measures after treatment in both groups with p< 0.05. Conclusions: Soft tissue massage along with joint and nerve mobilization is effective in symptoms severity and functional status. To further validate the findings of this study, similar investigations will need to be undertaken in the future to consider it before surgical intervention in CTS.